Revit Architecture 2012 intermediate - Polding, Jay (InifiniteSkills, 2011)
"In this Revit Architecture 2012 Tutorial, Jay Polding continues where he left off in the previous training course, advancing your knowledge of Revit Architecture 2012. You will apply what you learned in the first training course, and learn advanced techniques while working on a real project throughout this training video. Right from the beginning, you start setting up your files for working on this project. You quickly move onto working with a CAD survey, and into creating phases, using site tools, linking files, working on walls, floors, stairs, ramps and so much more. As you continue through this video based training course, you will watch Jay teach you how to setup area schedules, work on detailing, and finally, set up your presentation of the completed project, and share it using a walkthrough, and even printing to a PDF. By the completion of this advanced video tutorial, you will be fully capable of taking a Revit Architecture 2012 project from start to finish. You will have in-depth knowledge of the tools available to you, and how to effectively utilize them. Included are extensive working files so that you can learn by applying the training directly to the same files that the author is working on, right on your own computer."--Resource description page.